2019
DOI: 10.1097/md.0000000000017204
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pre-existing shoulder diseases and traumatic injuries of the shoulder on adhesive capsulitis in adult population

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…This contrasts with earlier investigations which suggested a higher risk of AC for white patients [ 54 ] but is supported by more recent and larger studies which also found higher rates in non-white patients [ 55 ]. Others have observed higher rates for Asian ancestry individuals in particular [ 13 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This contrasts with earlier investigations which suggested a higher risk of AC for white patients [ 54 ] but is supported by more recent and larger studies which also found higher rates in non-white patients [ 55 ]. Others have observed higher rates for Asian ancestry individuals in particular [ 13 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the known direct association between mastectomy and AC diagnosis [ 14 ], any beneficiaries that had a mastectomy (CPT 85.2, 85.3, 85.4) were excluded from the analysis. Patients with fracture, dislocations, and sprains involving the shoulder were also excluded as these are known causes of secondary AC [ 13 ]. Furthermore, because rotator cuff (RC) tears were used as our control group, any AC beneficiaries who had a concurrent RC diagnosis were also excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations